2015
DOI: 10.1037/pspa0000014
|View full text |Cite
|
Sign up to set email alerts
|

He did what? The role of diagnosticity in revising implicit evaluations.

Abstract: Research suggests that implicit evaluations are relatively insensitive to single instances of new, countervailing information that contradicts prior learning. In six experiments, however, we identify the critical role of the perceived diagnosticity of that new information: counter-attitudinal information that is deemed highly diagnostic of the target's true nature leads to a complete reversal of the previous implicit evaluation. Experiments 1a and 1b establish this effect by showing that newly-formed implicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
227
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(255 citation statements)
references
References 100 publications
(229 reference statements)
26
227
2
Order By: Relevance
“…8 Overall, the current findings support the idea that propositional processes play an important role in AA instruction effects on implicit evaluation. This conclusion is consistent with the growing body of evidence showing that (a) verbal instructions can have strong, immediate effects on implicit evaluations (Castelli et al, 2004;Gregg et al, 2006;Whitfield & Jordan, 2009) and (b) instruction-based changes in implicit evaluation depend on the operation of propositional processes (Cone & Ferguson, 2015;Peters & Gawronski, 2011b;Zanon et al, 2014). The current results extend these findings by showing that propositional processes also play a major role in AA instruction effects.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…8 Overall, the current findings support the idea that propositional processes play an important role in AA instruction effects on implicit evaluation. This conclusion is consistent with the growing body of evidence showing that (a) verbal instructions can have strong, immediate effects on implicit evaluations (Castelli et al, 2004;Gregg et al, 2006;Whitfield & Jordan, 2009) and (b) instruction-based changes in implicit evaluation depend on the operation of propositional processes (Cone & Ferguson, 2015;Peters & Gawronski, 2011b;Zanon et al, 2014). The current results extend these findings by showing that propositional processes also play a major role in AA instruction effects.…”
Section: Discussionsupporting
confidence: 82%
“…According to the APE model, any information that allows participants to entertain the proposition that a stimulus is positive or negative may instigate the proactive construction of new evaluative associations, which in turn may influence implicit evaluations. In line with this idea, changes in implicit evaluations have been observed when participants are provided with verbal information about the evaluative properties of a stimulus (Castelli, Zogmaister, Smith & Arcuri, 2004;Cone & Ferguson, 2015;Gawronski, Walther, & Blank, 2005;Gregg, Seibt, & Banaji, 2006). Importantly, these models predict a specific pattern of mediation such that instruction effects on explicit evaluation should mediate effects on implicit evaluation (e.g., Gawronski & Walther, 2008;Peters & Gawronski, 2011a;Whitfield & Jordan, 2009;see Gawronski & Bodenhausen, 2006;Case 4).…”
Section: Approach-avoidance Instruction Effectsmentioning
confidence: 69%
“…Much of cognition occurs unconsciously (32) and the topic of changing implicit responses has gained traction (18)(19)(20)(21)(22)(23)(24)27). As such, it will be crucial to understand the reaches of how these implicit responses might change, and Bayesian models may be highly useful.…”
Section: Discussionmentioning
confidence: 99%
“…However, other research has identified conditions under which implicit associations appear highly amenable to new information (20)(21)(22)(23)(24).…”
Section: Significancementioning
confidence: 99%
“…In the context of impression change, these ideas suggest that revision of implicit impressions may be strongest when new information is subjectively assessed as more diagnostic or important (though even propositional information that is seemingly low in diagnosticity may sometimes drive change; Van Dessel et al, 2016). In support of this possibility, Cone and Ferguson (2015) asked participants to read 100 behavioral statements about a novel person that indicated his overall goodness, and formed implicit positive impressions of him. After then learning an additional behavior that was extremely negative (e.g., that he had molested children), participants showed robust revision, switching to a strongly negative implicit impression of him.…”
mentioning
confidence: 99%